Small-Town Merchants are Not Using the Recommended Strategies to Compete Against Nationial Discount Chains: A Prescriptive Vs. Descriptive Study (Journal of Small Business Strategy (archive only), 2002)
The research question was: do small retailers use the strategies prescribed  in the literature for  them to compete with the large retail chains? Descriptive  survey results of 62 small business owner personal interviews indicate that they do not use three of the four prescribed marketing  strategies  to compete  with the large general  merchandise  discount  store chains. Respondents  were asked if they adjusted strategies after the major retailer moved in; 52% did not adjust product, 42% maintained the same price strategy, 21% did increase service strategy, and 50% did not alter promotion strategy. The findings revealed that 34% expanded their product line, with only 10% reducing their product line. Although not recommended, 37% actually dropped prices to compete. However, 77% did place a greater emphasis on service. Assessing the impact of these changes on financial performance, 58% indicated that their sales and profit margins had remained satisfactory  over a 5-year period  of measurement and a third (32%) had mixed results during the same time period.